2005
DOI: 10.4049/jimmunol.174.12.7986
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Mucosal and Parenteral Tuberculosis Vaccinations: Adenoviral-Based Mucosal Immunization Preferentially Elicits Sustained Accumulation of Immune Protective CD4 and CD8 T Cells within the Airway Lumen

Abstract: The mechanisms underlying better immune protection by mucosal vaccination have remained poorly understood. In our current study we have investigated the mechanisms by which respiratory virus-mediated mucosal vaccination provides remarkably better immune protection against pulmonary tuberculosis than parenteral vaccination. A recombinant adenovirus-based tuberculosis (TB) vaccine expressing Mycobacterium tuberculosis Ag85A (AdAg85A) was administered either intranasally (i.n.) or i.m. to mice, and Ag-specific CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
228
3
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(255 citation statements)
references
References 39 publications
22
228
3
2
Order By: Relevance
“…demonstrated that intranasal AdAg85a was able to elicit robust mucosal CD4 + and CD8 + T-cells responses in the airway lumen [34,36]. …”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that intranasal AdAg85a was able to elicit robust mucosal CD4 + and CD8 + T-cells responses in the airway lumen [34,36]. …”
Section: Resultsmentioning
confidence: 99%
“…In this regard, heterologous prime-boost vaccination schedules are highly attractive, since they can expand and activate both arms of the immune system. Ad vectors have been extensively used in the development of vaccines against diseases where a strong T-cell response is required (3,43,45,47). They are particularly attractive because of their intrinsic ability to induce a strong T-cell response characterized by high levels of IFN-␥ and cytotoxic activity (59).…”
Section: Discussionmentioning
confidence: 99%
“…Mice were first bled via the abdominal vessels and their lungs were exhaustively lavaged with PBS to remove bronchoalveolar lavage cells following our previously described protocol. 23 Lung granulomas were then isolated by using a well-established protocol. 24 -26 Briefly, the lavaged lungs were homogenized in a tissue blender (Waring Commercial, Torrington, CT) using the low speed setting for 10 to 15 seconds, which leaves the granulomas intact.…”
Section: Isolation Of Granuloma and Airway Luminal Cells From Mycobacmentioning
confidence: 99%
“…23,24,26 Purified airway luminal and granuloma cells were stained with antibodies against CD3, CD4, CD8, CD19, CD11c, Gr.1, CD11b, or NK1.1 and analyzed by FACS. The FACS analysis revealed the presence of CD3ϩCD4 ϩ (CD4 T cells), CD3ϩCD8ϩ (CD8 T cells), CD3-CD19ϩ (B cells), CD3-NK1.1ϩ [natural killer (NK) cells], CD11cϩ-CD11bϩ/Ϫ (CD11cϩ APCs), CD11c-CD11bϩ (CD11bϩ APCs), and CD11c-Gr.1ϩ (neutrophils) cell populations in both the airway lumen and granuloma (Table 1).…”
Section: Similar Immune Cellular Composition Observed In Airway Lumenmentioning
confidence: 99%